2021
DOI: 10.3390/ijms22041548
|View full text |Cite
|
Sign up to set email alerts
|

Size-Specific Copper Nanoparticle Cytotoxicity Varies between Human Cell Lines

Abstract: Commercially available copper nanoparticles of three different sizes were tested for cytotoxicity against three human cell lines using four different cytotoxicity assays. This array of data was designed to elucidate trends in particle stability, uptake, and cytotoxicity. The copper nanoparticles are not stable in cell culture media, and rapid changes over the time course of the assays play a critical role in the measured endpoints. Typically, the 40–60 nm particles tested were more cytotoxic than either smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Biocompatible agents containing copper in an inorganic form or in the context of metal–organic complexes are widely used in a variety of applications, largely as antibacterial and antifungal drugs, as well as in tumor treatment [ 1 , 2 , 3 , 4 , 5 ]. Copper oxide-based materials varying from sub-10 nm to 40–60 nm (nanoparticles; NPs) and fine (<10 µM) particles have demonstrated cytotoxicity against prokaryotic, yeast, mammalian cell lines and zebrafish embryos [ 6 , 7 , 8 , 9 ]. Coordination of Cu 2+ or Cu 1+ with complex organic scaffolds has yielded a number of perspective multi-targeting chemotypes with differential antitumor properties [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatible agents containing copper in an inorganic form or in the context of metal–organic complexes are widely used in a variety of applications, largely as antibacterial and antifungal drugs, as well as in tumor treatment [ 1 , 2 , 3 , 4 , 5 ]. Copper oxide-based materials varying from sub-10 nm to 40–60 nm (nanoparticles; NPs) and fine (<10 µM) particles have demonstrated cytotoxicity against prokaryotic, yeast, mammalian cell lines and zebrafish embryos [ 6 , 7 , 8 , 9 ]. Coordination of Cu 2+ or Cu 1+ with complex organic scaffolds has yielded a number of perspective multi-targeting chemotypes with differential antitumor properties [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…An L929 mouse fibroblast cell line is conventionally used for biocompatibility evaluations [ 30 ], while HaCaT is a human epidermal keratinocytes line and was chosen as a representative cell model due to the potential use of PU-EM-CuNPs as wound-dressing materials, nonwoven materials for surgical masks and personal protective equipment production, or other applications that imply a direct contact of the membrane with the skin. As for other metal or metal-oxide particles, such as silver NPs, the cytotoxic effect of CuNPs depends on their size, shape, and concentration [ 21 , 31 , 32 , 33 ]. For instance, Na and Kennedy tested the cytocompatibility of CuNPs towards three human cell lines and reported that particles of 40–60 nm are cytotoxic due to a high cellular intake, while bigger or smaller particles are less up-taken but cause higher oxidative stress [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for other metal or metal-oxide particles, such as silver NPs, the cytotoxic effect of CuNPs depends on their size, shape, and concentration [ 21 , 31 , 32 , 33 ]. For instance, Na and Kennedy tested the cytocompatibility of CuNPs towards three human cell lines and reported that particles of 40–60 nm are cytotoxic due to a high cellular intake, while bigger or smaller particles are less up-taken but cause higher oxidative stress [ 31 ]. Similarly, Semisch et al proved that CuO micro-particles exerted no cytotoxicity in a range up to 50 µg/mL, while CuO NPs have a pronounced cytotoxic effect [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Сравнительное исследование на крысах наночастиц (25 нм) и микрочастиц меди (14-25 мкм) in vivo показало, что наночастицы Cu вызывали повреждение эритроцитов, тимуса, селезёнки, печени и почек при дозе ≥ 200 мг/ кг в сутки, но микрочастицы не вызывали каких-либо побочных эффектов даже в самой высокой дозе ≥ 400 мг/кг в сутки. Авторы полагают, что большая площадь поверхности и высокая растворимость в физиологической среде наночастиц напрямую повлияли на токсикологические реакции и биораспределение при пероральном введении [66].…”
Section: токсичность наночастиц меди и оксидов медиunclassified